The Anthropocene and the great transformation: Perspectives for critical governance and transformation research in the spatial sciences - Antje Bruns (Spatial transformation: Processes, strategies, research design, 2022)
This article critically examines the new guiding concept of transformation in the spatial sciences with regard to its underlying narrative - namely the Anthropocene. Without such an examination, spatial science research might contribute to apolitical, spatially undifferentiated and Eurocentric governance and transformation research. Hence, I propose to place political aspects and questions of power more firmly in the focus of theoretical, methodological and empirical interest and to take up a general perspective of inequality. Plurality and diversity (from a social and spatial perspective as well as with regard to knowledge production) therefore become the central transverse dimensions of governance and transformation research, which should essentially be reflexive.
urn:nbn:de:0156-08910432; hdl:10419/251347; https://econpapers.repec.org/RePEc:zbw:arlfob:19
Keywords: 710; Epistemological orientation; problem framing; reflexivity; knowing and nonknowing; provincialising theories and practices